De La Politique De Santé Publique Aux Démarches D’entraide Sociale : Mutuelles De Santé Et Équité Sociale Dans Le Département Du Borgou Au Bénin - Yvette Onibon Doubogan; Agnès Oladoun Badou Savi; Roger A. Atchouta (European Scientific Journal, ESJ, 2017)
Apart from its impact on the improvement of health care system, the mutual health insurance implies some changes on the management of health care at family level. This study analyzes the role played by mutual health insurance in the promotion of social equity within families in the Department of Borgou (North -east Benin). It also focuses on qualitative research methodology which combines documentary analysis, life experiences recounting and direct observation for data collection. The empirical corpus triangulation based on the theoretical perspective to social reinforcement of gender roles from Vidal (2008) reveals that the operationalization of insurance systems in Benin cotton basin which has contributed to a redefinition of gender roles in terms of family health care. At the event of mutual health insurances, the responsibilities in terms of family health care formerly devoted exclusively to women, are highly in a movement and then, are shared between wife and husband inner the couple. The mutual health insurance systems affect the private sphere and have influenced the existing relationship between men and women on the health care where, men have to play an important role towards family health care.